Budget impact analysis of the use of paricalcitol for the treatment of secondary hyperparathyroidism in chronic kidney disease - Lorenzoni, Valentina; Turchetti, Giuseppe (Farmeconomia. Health Economics and Therapeutic Pathways, 2014)
OBJECTIVE: Evaluation of the budget impact of the use of paricalcitol (compared to alternative treatment) for secondary hyperparathyroidism (SHPT) in patients with chronic kidney disease (CKD) when used at two different timing of therapy. METHODS: Two Markov models related to a different timing of treatment have been developed: the intermediate stage of chronic kidney disease (CKD3) and the dialysis stage. The analysis was conducted with the perspective of the Italian National Health System and over a 5-year time horizon. The clinical and economic data used in the model were derived from the literature and other assumptions were made based on the opinion of clinical experts. Univariate sensitivity analysis was conducted to test the robustness of the results. RESULTS: The base case shows that starting paricalcitol treatment from the dialysis stage (considering 13,311 possible candidates) is associated with a reduction in direct costs from € 1,782,921,351 to € 1,622,357,209 over 5 years. Furthermore, considering a collective of 1,000 subjects eligible and starting treatment with paricalcitol since the intermediate stages of the CKD, is associated with an overall cost saving of € 1,197,500. DISCUSSION AND CONCLUSIONS: Paricalcitol is expected to be cost-saving in patients with SHPT in Italy considering both the therapeutic indications of the drug. Moreover, despite the higher cost of using paricalcitol in pre-dialysis stage, an early treatment of SHPT determine an overall decrease in direct medical costs.